Serum Biochemical, Hormonal and Fatty Acid Profiles During the Late Gestation of Pregnancy Ketosis in Boer Cross Goats - A. A. Affan; FMA Amirul; AAA Ghani; S Annas; M Zamri-Saad; HA Hassim (Jurnal Ilmu Ternak dan Veteriner, 2018)
Pregnancy ketosis has been recognized as one of the common metabolic disease affecting goat’s meat and milk production. For the present study, sixteen (n=16) individuals of pregnant does at day 80 of pregnancy had been used. A total of 8 does were categorized as control group (healthy pregnant goats), were fed on Napier grass and goat concentrate with water ad libitum, and another 8 does were considered as treatment group which categorized as ketosis based on the clinical signs and presence of ketone body in urine. Blood sample were collected from all goats for biochemical profiles analysis which were glucose, Beta-hydroxybutyrate (BHBA), free fatty acid (FFA), calcium, electrolytes (sodium, potassium, chloride), liver enzyme and hormonal levels (cortisol and insulin). Three does from each group were slaughtered and liver samples were collected for fatty acid profiles study. In this study, the BHBA, FFA, calcium, amino aspartate transferase (AST), gamma glutamyl transferase (GGT) and cortisol hormone were significantly higher in pregnancy ketosis goats as compared to control group. Meanwhile, the concentration of glucose, sodium, potassium, chloride and insulin hormones were lower in pregnancy ketosis goats as compared to control. Furthermore, the fatty acid composition in blood plasma of pregnant goat with ketosis showed higher level of palmitic, stearic and oleic acid, while in liver, palmitic, oleic and linoleic acid was found higher.